CAUTIOUS DECISION MAKING IN OBSESSIVECOMPULSIVE DISORDER: THE ROLE OF PERCEPTUAL UNCERTAINTY AND IMPLICIT INCENTIVES. Issue 9 (13th August 2015) - Banca, Paula; Vestergaard, Martin D; Rankov, Vladan; Baek, Kwangyeol; Mitchell, Simon; Lapa, Tatyana; Castelo-Branco, Miguel; Voon, Valerie
Abstract : Objective: The compulsive behaviour underlying Obsessive-Compulsive Disorder (OCD) may be related to abnormalities in decision-making. The inability to commit to ultimate decisions, e.g. patients unable to decide whether their hands are sufficiently clean, may reflect failures in accumulating sufficient evidence prior to a decision. Here we investigate the process of evidence accumulation in OCD in perceptual discrimination, hypothesizing enhanced evidence accumulation relative to healthy volunteers. Method: Twenty-eight OCD patients and 35 healthy control subjects were tested with a low-level visual perceptual task (random dot motion task), whereby different coherent levels for motion were defined to measure high and low uncertainty, and two response conflict tasks as control tasks (flanker task and probabilistic selection task). Logistic regression analysis across all coherence levels (which accounted for visual detection threshold) and hierarchical drift diffusion modelling (HDDM) were used to characterize response strategies between patients with OCD and healthy controls in the random dot motion task. Results: Patients required more evidence under high uncertainty perceptual contexts, as indexed by longer response time and higher decision boundaries. HDDM, which defines a decision when accumulated noisy evidence reaches a decision boundary, further showed slower drift rate towards the decision boundary reflecting poorer quality of evidence entering the decision process in patients under low uncertainty. With monetary incentives emphasizing speed, patients decreased the decision thresholds relative to controls, accumulating less evidence in low uncertainty. These findings were unrelated to visual perceptual deficits and response conflict. Conclusion: This study provides evidence for impaired decision-formation processes in OCD, with a differential influence of high and low uncertainty contexts on evidence accumulation (decision threshold) and on the quality of evidence gathered (drift rates). It further emphasizes that OCD patients are sensitive to monetary incentives heightening speed in the speed-accuracy tradeoff, improving evidence accumulation and shifting away from pathological internal monitoring. These findings may have relevance for therapeutic approaches.